ANALISIS PERBANDINGAN ASURANSI SYARIAH DAN KONVENSIONAL (STUDI POLIS PT. PRUDENTIAL LIFE ASSURANCE) - Nurhadi . (UIN Mataram, 2019)
Risk control carried out by transferring the risks experienced by the insured to theinsurer is called insurance. The development of Islamic insurance is relatively goodcompared to similar financial businesses, especially the conventional financial industry.The research objective is to find out how the comparison of conventional and Islamicinsurance so that more consumers prefer Sharia insurance at PT. Prudential LifeAssurance. This type of descriptive research with a qualitative approach, namelycollecting data to describe or affirm a concept or symptom, also answer questionsrelated to the status of the subject of research. The results of this study PT. PrudentialLife Assurance has many components that are very different from other insurance. It isexpected that PT. Prudential Life Assurance will continue to survive with componentsthat are more profitable to customers, so as to increase the growth of policy every year.Keywords: Analysis, Comparison, Sharia Insurance, Conventional Insurance.